Torbangun (Coleus amboinicus Lour) extracts affect microbial and fungus activities - Khattak, Muhammad Muzaffar Ali Khan; Bakhtiar, M. Taher; Damanik, Muhammad Rizal Martua; Abdul Rahman, Suzanah; Abu Bakar, Ibrahim; Yahaya, Azhary (Lifescience Global, 2013)
Coleus also known as Torbangun or Ati Ati plants leaves i.e. Coleus amboinicus Lour from Indonesia (CAL-I) and Coleus aromaticus (CAT-M), Pogostemon cablin (PC-M), Coleus blumei–red leaves (CBR-M), Coleus amboinicus– (CAL-M) Coleus blumei –purple leaves (CBP-M) from Malaysia were collected, freeze dried and extracted with aqueous methanol. The effect of the extract was assessed on microbial and fungal activities in relation to their phytochemicals and antioxidants concentrations. The total phenolic content was determined according to the Folin-Ciocalteu method whilst antioxidant activity was assessed using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method. The anti-microbial and anti-fungal activities were assessed by minimum inhibitory concentrations (MIC) and disc diffusion methods. The result indicates that the extracts are rich sources of phytochemicals and antioxidants from the listed plants. When the effect of the extracts was assessed on microbial and fungal activities it was observed that the effect was more pronounced on the gram-positive bacteria compared to gram-negative bacteria. Furthermore, there was strong association between phytochemicals and antioxidants concentration and with the microbial and fungal activities. However, it was not consistent for all types of strains. This study shows that Torbangun plants extracts are rich in phenolic contents therefore; it can be used as free radical scavengers and antimicrobial agent apart from other traditional uses.